Sosialisasi dan Demonstrasi Cuci Tangan Pakai Sabun pada Siswa Sekolah Dasar Kelas 4 dan 5 di Kecamatan Wanea Kota Manado - Sapulete, Ivonny Melinda; Sapulete, Margaretha Rosalinda; Sumampouw, Oksfriani Jufri; Nelwan, Jeini Ester (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
Background: The habit of handwashing with soap (HWWS) can significantly reduce the risk of diarrhea, lowering the incidence by approximately 42–47%. Promoting HWWS practices can help save nearly one million lives globally. This highlights that HWWS is one of the simplest yet most impactful actions for reducing the transmission of infectious diseases, particularly among elementary school students. One of the key problems observed is that many students frequently fall ill, partly due to the lack of regular HWWS habits. The aim of this activity was to assess the impact of health education on students' knowledge regarding HWWS. Methods: This activity was conducted on Friday, September 6, 2024, starting at 08:00 AM until completion. Health education was delivered by Dr. Ivonny Sapulete, MSc, along with a team of master's students from the public health sciences program. The session lasted for two hours and concluded with a social gathering. A total of 60 students and teachers participated in the event. To evaluate the impact, students' knowledge was assessed before and after the health education session through a brainstorming method. Results: The results of this activity showed that there was a noticeable improvement in students’ knowledge about HWWS, as indicated by the brainstorming sessions conducted before and after the health education session. The differences observed demonstrate that the educational intervention positively influenced students’ understanding of proper hand hygiene practices. Conclusion: In conclusion, this educational activity successfully increased students' knowledge about handwashing with soap. Health promotion efforts such as this are essential in instilling good hygiene habits in children from an early age.